Design and Simulation of Shoulder Joint Rehabilitation Robot based on the Method of Nerve Repairment - Zhao Yuanhao; Cui Bingyan; Huang Jinfeng; Xiao Jingjin (Jixie chuandong)
The rehabilitation of the upper limbs of human body is determined by the recovery of shoulder joint movement function. Based on the analysis of the shoulder joint physical characteristics and movement characteristics of the shoulder joint,according to shoulder rehabilitation exercise training requirements,a novel shoulder joint rehabilitation robot is designed based on 3- DOF series- parallel mechanism. The shoulder joint has three rotation degrees of freedom and can complete three- dimensional composite sports. The series- parallel mechanism is adopted to ensure the neutral and stability of mechanism,and the mechanism movement space is increased. By using the Creo software,the three- dimensional modeling of the shoulder joint rehabilitation robot is carried out. According to the methods of nerve repairment,aiming at the rehabilitation of shoulder joint in soft paralysis,the shoulder joint rehabilitation robot is simulated. The results of the analysis show that the shoulder joint rehabilitation robot can meet the needs of patients with soft paralysis,and the design of the shoulder joint rehabilitation robot is reasonable. It laid a theoretical foundation for the design and research of shoulder rehabilitation robot.